The Evolution of Content Marketing : Analysis of Trend Product and Their Impact on Customer Loyalty at Bank Mestika, North Sumatra: Evolusi Konten Marketing : Analisis Tren Produk dan Dampaknya terhadap Loyalitas Konsumen Bank Mestika Sumatera Utara - Catherine Catherine; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This research is motivated by the high customer turnover rate at Bank Mestika in North Sumatra, caused by the lack of relevant content marketing and the slow adaptation of trend product to the needs of modern customers. The purpose of this study is to examine the influence of content marketing and trend product on customer loyalty and to identify the synergy between these two variables in forming emotional bonds and customer loyalty behavior. The techniques used include a questionnaire survey and purposive sampling of customers who have been active for at least two years. The data analysis method applies Partial Least Square Structural Equation Modeling to test the validity, reliability, path coefficient, effect size, and predictive relevance of the research model. The results show that content marketing partially and simultaneously has a positive and significant effect on customer loyalty with a moderate effect strength, as well as trend product that provide a similar contribution to customer loyalty. The model's explanatory value reaches a high level and its predictive relevance supports strategic decisions for Bank Mestika in designing integrated content marketing and trend product to strengthen customer loyalty.